What's so funny? : my hilarious life - Conway, Tim.; Scovell, Jane, 1934-; Burnett, Carol (New York : Howard Books, a division of Simon & Schuster, Inc., 2013)
Six-time Emmy Award-winning funnyman Tim Conway, best known for his characters on The Carol Burnett Show, offers a straight-shooting and hilarious memoir about his life on stage and off as an actor and comedian
My beginnings -- Growing up and liking it -- Chagrin Falls -- School days: part deux -- A little higher learning -- You're in the Army now -- Let the laughs begin -- Be it ever so humbling (and it was) -- The importance of being Ernest Anderson -- Hi ho Steverino -- Married with children -- The family guy -- Back to business -- The importance of being Ernest Borgnine -- A salute to Garry Moore -- All roads lead to Carol -- Heaven -- Harvey -- The end of the affair -- Old friend, new beginning -- They're off and running! -- A little friend-dropping -- Golf -- The birth of Dorf -- Trodding the boards -- Epilogue -- Fooled you!
Keywords: Conway, Tim; Comedians -- United States -- Biography; Actors -- United States -- Biography